Ruptures in Existence - Openings for the Future: The Need for a Different Resource Landscape - Nilsson, Annika E. (Journal of Northern Studies, 2021)
Taking the once seemingly constant yet constantly moving Arctic sea ice as inspiration, this article reflects on how individuals and societies can navigate the ruptures in our expectations about a predictable future caused by climate change. With insights from scientific assessments of adaptation and resilience in the Arctic, it describes various facets of a resource landscape for addressing the challenges brought by the new reality of a warmer and more unpredictable world. In focus is the central role of people, including their learning processes and ability to cooperate. It furthermore emphasizes that futures and values are the outcome of social processes, not predetermined, and thus in the hands of those who engage in shaping them.